Determinants of Overall Quality of Life in Patients with Multiple Sclerosis: PLS-MGA Evidence from Kuwait - Alanezy, Mashail S A O; Azman, Azlinda; Singh, Paramjit Singh Jamir; Alenezi, Fahad Neda G (Migration Letters, 2024)
Purpose – This paper aims to identify the determinants of overall quality of life (QoL) in PwMS and explore whether there was any significant difference between the path coefficients for males and females. Design/methodology/approach – Data were collected by distributing questionnaires to 230 PwMS receiving healthcare services in Bin-Sina and Al-Ameri hospitals in Kuwait. The data were analyzed using partial least squares structural equation modeling (PLS-SEM) and multi-group analysis (MGA) in SmartPLS 3.0 software. Results – The study’s findings demonstrate a positive and significant relation between psychosocial support services and the overall QoL for male PwMS. Additionally, the results of the MGA indicate that the effect of psychosocial support services on overall QoL is stronger for male PwMS than their female counterparts. Psychological resilience is a particularly influential factor in the overall QoL of both male and female groups. Furthermore, the MGA results suggest no significant differences in the relationship between psychological resilience and overall QoL across both groups. Originality/value – Although several scholars discuss the factors influencing overall QoL, This study is among the first few in the Arab world that have systematically evaluated the effect of psychosocial support services and psychological resilience on the overall QoL in PwMS. In addition, so far, no studies have effectively made a comparative analysis across genders, i.e., psychosocial support services and psychological resilience are personal factors in the determinants of overall QoL significantly different across genders.